Relevansi Paradigma Filsafat Ilmu Terhadap Perkembangan Metode Penelitian Ilmiah Kontemporer - Firanita Putri; Siminto; Yatin Mulyono (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the relevance of the philosophy of science paradigm to the development of contemporary scientific research methods. The study uses a literature study method by examining primary sources in the form of original works by leading philosophers of science and methodologists, as well as secondary sources in the form of articles from national scientific journals indexed by SINTA and international journals indexed by Scopus and Web of Science published in the period 2015–2024. Data are analyzed through a process of identification, classification, comparison, and synthesis of findings to examine the relationship between the philosophy of science paradigm and the development of research methodology. The results of the study show that each research approach, whether quantitative, qualitative, or mixed methods, is based on different ontological, epistemological, and axiological assumptions according to the adopted paradigm. The paradigm shift from positivism to post-positivism, constructivism, and pragmatism also influences how researchers understand reality, acquire knowledge, and determine the research methods used. These findings emphasize that understanding the philosophy of science paradigm plays a crucial role in maintaining the consistency, validity, and meaningfulness of scientific research. Therefore, strengthening paradigmatic literacy is a fundamental need for researchers to produce research that is more reflective, valid, and relevant to contemporary scientific developments.